Construction of amperometric biosensor modified with conducting polymer/carbon dots for the analysis of catechol. Issue 23 (21st October 2020) - Yasa, Mustafa; Deniz, Aybuke; Forough, Mehrdad; Yildirim, Erol; Persil Cetinkol, Ozgul; Udum, Yasemin Arslan; Toppare, Levent
Abstract: Phenolic compounds used in food industries and pesticide industry, are environmentally toxic and pollute the rivers and ground water. For that reason, detection of phenolic compounds such as catechol by using simple, efficient and cost‐effective devices have been becoming increasingly popular. In this study, a suitable and a novel matrix was composed using a novel conjugated polymer, namely poly[1‐(5‐(4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1, 2‐b:4, 5‐b']dithiophen‐2‐yl)furan‐2‐yl)‐5‐(2‐ethylhexyl)‐3‐(furan‐2‐yl)‐4H thieno[3, 4‐c]pyrrole‐4, 6(5H)‐dione] (PFTBDT) and carbon dots (CDs) to detect catechol. PFTBDT and CDs were synthesized and the optoelectronic properties of PFTBDT were investigated via electrochemical and spectroelectrochemical studies. Laccase enzyme was immobilized onto the constructed film matrix on the graphite electrode. The proposed biosensor was found to have a low detection limit (1.23 μM) and a high sensitivity (737.44 μA/mM.cm −2 ) with a linear range of 1.25–175 μM. Finally, the applicability of the proposed enzymatic biosensor was evaluated in a tap water sample and a satisfactory recovery (96–104%) was obtained for catechol determination. Abstract : An amperometric biosensor for the detection of catechol is constructed through the immobilization of laccase enzyme on carbon dot (CD) modified conducting polymer film matrix on the graphite electrode. The enzyme‐based biosensor, optimized with regards to amount of CDs, polymer, enzyme unit, and pH, is found to be highly selective and sensitive with a limit of detection (LOD) of 1.23 μM and applicable to use in tap water samples.